Systematic Review and Meta-Analysis of the Birth Prevalence of Orofacial Clefts in Low- and Middle-Income Countries. (September 2017) - Kadir, Ayesha; Mossey, Peter A.; Orth, M.; Blencowe, Hannah; Sowmiya, Moorthie; Lawn, Joy E.; Mastroiacovo, Pierpaolo; Modell, Bernadette
Background: In the last comprehensive review of the literature published in 2002, little information on the prevalence of orofacial clefts was available from low- and middle-income countries (LMICs). Objective: To analyze published data on the birth prevalence of cleft lip and/or palate ( CL/P) from LMIC. Design: Systematic review of the literature and meta-analysis of data from original papers on the birth prevalence of cleft lip and/or cleft palate (CL/P) in LMICs between 1990 and 2014. Secondary inclusion criteria were developed to analyze lower-quality studies from countries with scarce data. Main Outcome Measure: Birth prevalence of undifferentiated CL/P (with or without associated syndrome or other anomaly). Results: Twenty-eight studies met strict inclusion criteria. Among 31, 475, 278 total births, the pooled birth prevalence of undifferentiated CL/P was 1.38 per 1000 births (95% confidence interval [CI]: 1.20 to 1.56). Four studies met criteria for secondary analysis, providing data on 75, 627 births, with a pooled prevalence of 0.75 CL/P cases per 1000 births (95% CI: 0.56 to 0.95). Comparison of studies was limited by variable definitions of cases and of the reference population and by inconsistent reporting of outcomes. There is significant heterogeneity in the findings. Conclusions: In LMICs, approximately 1 in every 730 children is born with CL/P. To optimize comparability across settings, future research should use a standard classification system and standard criteria for data collection and presentation. As clefting is associated with deprivation, understanding the true scale, risks, and preventive measures for orofacial clefts in LMIC is a matter of both scientific and humanitarian importance.